2004
DOI: 10.1007/s00383-002-0775-6
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis in children less than 3 years of age: a 28-year review

Abstract: Appendicitis is the most common surgical abdominal emergency in the pediatric population, but is rarely considered in children less than 3 years of age. The goal of this study was to identify the presenting symptoms and signs in this age group and examine their subsequent management and outcome. A 28-year experience of a single pediatric surgeon in academic practice was reviewed; 27 children less than 3 years old (mean 23 months) comprised 2.3% of all children with appendicitis in his series. The most common p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
80
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 13 publications
6
80
1
7
Order By: Relevance
“…We assume this is because we included children of all pediatric ages, from 1 - years, and the fact that the frequency of acute appendicitis is relatively low in children aged ≤ 3 years. Among the 119 acute appendicitis patients, only two were ≤ 3-years-of-age (1.6%), similar to result reported by Alloo et al [6].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We assume this is because we included children of all pediatric ages, from 1 - years, and the fact that the frequency of acute appendicitis is relatively low in children aged ≤ 3 years. Among the 119 acute appendicitis patients, only two were ≤ 3-years-of-age (1.6%), similar to result reported by Alloo et al [6].…”
Section: Discussionsupporting
confidence: 87%
“…The diagnostic approaches of two scoring systems [10,21] have been verified as being useful in diagnosis [8,9]. However, the diagnostic value of fever or leukocytosis is debatable [3,6,[12][13][14]21]. Monneuse et al analyzed 326 patients suspected of acute appendicitis prior to surgical intervention and reported that fever or leukocytosis was not detected in 15.6% of the patients [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11,12,19] However, children with complicated AA were significantly younger than those with simple AA. In the group of children up to 5 years old, more than 50% cases of AA were complicated, [22][23][24] probably because the diagnosis of complicated AA is a particularly difficult one in this age group. Interestingly, the negative appendicectomy rate in this series was similar in all age groups.…”
mentioning
confidence: 99%